The Socialization of Halal Certification and PIRT to MSME Actors in Waringin Jaya Village, Bojong Gede, Bogor - Sukma, Gregorius Teja; Haryani, Heni; Wahyuni, Yanti Sri; Widiyati, Dian (The Future of Education Journal, 2026)
This community service aims to enhance the understanding and skills of Micro, Small, and Medium Enterprises (MSMEs) in Waringin Jaya Village, Bojong Gede Subdistrict, Bogor Regency, regarding the importance of business legality through Halal Certification and PIRT (Traditional Food Production License). The lack of knowledge among MSME actors about procedures, regulations, and the benefits of certification has led to low product competitiveness and limited market access. The activity was carried out through socialization, technical training, and administrative assistance for certification applications in accordance with the provisions of BPJPH (Indonesian Halal Certification Agency) and BPOM (National Agency of Drug and Food Control). The implementation methods included preparation, site observation, coordination with related agencies, material socialization, technical training for registration, and activity evaluation. The results of the activity showed an increase in participants’ understanding of the urgency of Halal certification and PIRT, as well as their ability to prepare the necessary documents. Through this activity, MSME actors are expected to meet product safety and halal standards, increase consumer trust, and expand local product marketing opportunities. In conclusion, this discussion asserts that Halal certification and PIRT licenses are mandatory for MSME actors selling various products and must be familiar with the regulations regarding Halal Certification and PIRT Licenses.